Pengelolaan Sektor-Sektor Publik Ekonomi dalam Kompilasi Hukum Ekonomi Syariah - Azizah Azis (Institut Agama Islam Negeri (IAIN) Bone, 2018)
This paper is intended to add scientific insight into the management of the Islamic economic sector, especially in managing the public sectors of the economy. The problem raised in this paper is the position of the public sectors of the economy in meeting the basic needs of the community and managing public assets or state assets as part of the public sector of the economy in increasing state revenues according to the Compilation of Sharia Economic Law. The economic sector-public sector should be understood more than just an idea, given the vastness and breadth of this section managed by individuals or partners who ignore the interests and benefits of the people. As it is understood together, the public economic sectors basically provide and guarantee the availability of an infrastructure to improve the fulfillment of the economic needs of the community, in addition to being a sector that produces goods and services for defense education, and security as well as everything related to the public sector economy. Thus, this paper can present implications in accordance with the aims and objectives.